Pemberian Video Edukasi terhadap Pengetahuan tentang Pendewasaan Usia Perkawinan (PUP) pada Remaja - Zuhairi Lubis; Yora Nopriani (Jurnal Kesmas Asclepius, 2023)
This study aims to determine the effect of video in increasing knowledge about maturing marriage age in young SMK Bakti Ibu 3 Palembang students. This research method uses a pre-experimental design with a pre-post-test design with a control group. The results showed that 18 respondents (45%) had a low level of knowledge, 20 respondents (50%) had a sufficient level of expertise, and 2 respondents (5%) had a good level of understanding. The analysis results using the t-test were obtained (p-value 0.000). In conclusion, providing educational videos can increase respondents' knowledge about maturing at the age of marriage. Keywords: Knowledge, Marriage, Youth, Video